MicroRNA-1275 targets PKCα to depress proliferation and the invasion of pancreatic cancer cells - Yuan, Lei; Ji, Meng-Yao; Lu, Cheng; Huang, Pingxiao; Dong, Wei-Guo (Translational Cancer Research, 2018)
Background: Pancreatic cancer (PC) is one of the cancers with the highest mortality rate in the world. Therefore, it is urgent to understand the potential molecular mechanisms of PC progression and to detect novel and original strategies for a targeted therapy. Many reports show that a lot of cancers are regulated by miR-1275; however, the role which miR-1275 plays in PC remains unknown. Our study was conducted to explore miR-1275 expression and role in PC. Methods: qRT-PCR was used to detect the expression of miR-1275 in both PC tissues and cell lines. The function of miR-1275 in PC cells was evaluated by luciferase assays through transfection with miR-1275 mimics and inhibitor. Western blot analysis was employed to test the target gene expression of miR-1275. Results: Reduced miR-1275 expression in the PC tissues was observed in comparison with the matched non-cancerous tissues. Furthermore, over-expression of miR-1275 significantly inhibited cell proliferation, metastasis, and invasion in the PC cells. In addition, we found that protein kinase C (PKCα) is negatively controlled by miR-1275 at the posttranscriptional level, through a pathognostic target spot within the 3'-UTR. In PC and cell lines, the expression of PCKα is usually up-regulated and adversely related to miR-1275 expression. Conclusions: The results of our data are first to show that miR-1275 was a new suppressor and negative regulator of PKCα expression in PC, possibly furnishing a new method for PC therapy.